The severe exercise domain amplitude: a comparison between endurance runners and cyclists - Raimundo, J.; Turnes, T.; de Aguiar, R.; Lisbôa, F.; Loch, T.; Ribeiro, G.; Caputo, F. (Research Quarterly for Exercise and Sport, 2019)
Purpose: Metabolic perturbation and VO2 on-kinetics are potential modifiers of fatigue and vary in importance depending on the exercise task. Thus, performance fatigability during high-intensity exercise seems to be exercise mode dependent, affecting tolerance in the severe domain. However, the effects of exercise mode on severe domain amplitude are still unknown. The aims of this study were to compare the severe domain amplitude in endurance runners and cyclists and to verify its possible determinants. Methods: Ten runners and eleven cyclists were tested to determine VO2max, maximal velocity/power output of incremental test (vVO2max/pVO2max), critical velocity/power (CV/CP), distance/work above CV/CP (D'/W'), and the highest velocity/power output which VO2max is attained during constant exercise (VHIGH/PHIGH). The severe domain amplitude was considered as VHIGH/PHIGH relative to CV/CP. Results: When normalized by vVO2max/pVO2max, although VHIGH and PHIGH were similar, CV (89.0 ± 2.2% vVO2max) was higher than CP (84.0 ± 4.1% pVO2max; p < .05; ES = 1.51). Consequently, the severe domain amplitude was higher in cyclists (153.6 ± 14.4% CP vs. 137.2 ± 14.6% CV; p < .05; ES = 1.13). Runners presented faster VO2 on-kinetics than cyclists at VHIGH/PHIGH. The severe domain amplitude was correlated with D' (r = .65) and W' (r = .71), but not with VO2 on-kinetics. Conclusions: Cyclists have a lower CP (%pVO2max) and a greater severe domain amplitude than runners, providing a greater range of intensities for attainment of VO2max. Furthermore, the severe domain amplitude appears to be linked to finite energy reserves, but unrelated to VO2 on-kinetics.